Perbandingan pelapisan kitosan dan beeswax terhadap kualitas fisikokimia jeruk siam di Badan Standarisasi Instrumen Pertanian Tanaman Jeruk dan Buah Subtropika (BSIP JESTRO) Kota Batu - Jannah, Fittriyah Roudhotul (Maliki Interdisciplinary Journal, 2024)
Citrus nobilis Lour, also known as Siamese orange, is a citrus fruit that has been widely developed in Indonesia due to its high level of production and popularity among consumers. The prospect of Siamese orange development has had a positive impact. The problem that often occurs with post-harvest oranges (Citrus sp.) is that they are easily damaged due to their high water content. For that, we need a coating that can suppress the problems that occur. Coating materials that are often used are chitosan and beeswax. This study aims to determine the effect of chitosan and wax coating on the shelf life and physical-chemical conditions of the Pontianak variety and the honey variety. The study consisted of three treatments and three replications. The study's results were analyzed using one-way variance analysis (ANOVA) to determine the effect of coating on the physicochemical quality of Siam Pontianak oranges and honey. Coatings of chitosan and wax had an effect on the physicochemical qualities of the Pontianak Siamese oranges and Honey Siamese oranges during the storage period. The best use of coatings is wax (beeswax) because it has an effective effect on several quality parameters of Siamese oranges compared to control and chitosan coatings, such as reducing weight loss, maintaining diameter, total dissolved solids, and intensity of damage.